The Phenomenon of Phubbing and Moral Degradation Among Adolescents in Parent–Child Communication Interactions - Iftiya Salwa Tuanany; Andi Fitriyani; M. Ihwan F. Putuhena; Salma Hayale (IAIN Ambon, 2024)
This study aims to analyze the phenomenon of phubbing among adolescents in RT 007/RW 017 Dusun Kahena, including the forms of phubbing behavior, its contributing factors, and its impact on the degradation of social relationships and moral values in communication, both among adolescents and between parents and children. The research employs a qualitative approach, using data collection techniques such as observation, interviews, and documentation, involving both adolescents and parents as research subjects in order to obtain an in-depth understanding of the phenomenon occurring within the community. The results of the study indicate that phubbing behavior occurs intensively in the daily lives of adolescents, characterized by the habit of gathering without direct interaction due to a strong focus on smartphone use, such as accessing social media and playing games. The high duration of smartphone usage, even reaching up to 24 hours for some individuals, reflects a significant level of technological dependency. The factors influencing this behavior include dependence on technology, peer pressure, low awareness of communication ethics, and a lack of positive alternative activities. The impact of phubbing behavior is the degradation of social relationships, as evidenced by the decline in communication quality, including reduced openness, empathy, trust, equality, and supportive attitudes. Furthermore, phubbing contributes to moral degradation in communication between parents and children, which is marked by reduced responsiveness from children, a tendency to be defiant, and a decline in social attitudes and behavior due to a lack of parental attention, imbalance in technology use, unclear value systems, and limited emotional communication.